Do performance ranks increase productivity? Evidence from a field experiment - Anik Ashraf (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Can a firm increase its workers' eff ort by introducing competition through performance-based ranking? On one hand such ranking can increase eff ort because of individuals' desire for status from high ranks, but on the other, it can demotivate them or make them wary of outperforming peers. This paper disentangles the e ffects of demotivation, social conformity, and status associated with ranking through a randomized experiment at a Bangladeshi sweater factory. Treated workers receive monthly information on their relative performance either in private or in public. Both a simple theoretical framework and empirical evidence from the field show that workers' intrinsic desire to be good at work induces privately ranked workers to increase eff ort upon receiving positive feedback, but they get demotivated and decrease e ffort upon receiving negative feedback. Public ranking lead to lower net eff ort relative to private ranking because of a strong preference not to outperform friends. The negative e ffects from demotivation and social conformity may explain why the existing literature finds mixed evidence of impact of ranking workers.
Keywords: D23; J53; O15; 330; Peer Effects; Productivity; Rank Incentives